Synthesis, Characterization and Thermal Properties of Polythiophene Composites - Nemade, K.R.; Waghuley, S.A. (Asian Journal of Chemistry, 2012)
Polythiophene (PTh) and its composites are currently subject of intense investigation due to their wide application in electronic, gas sensing and optoelectronic devices. The stability of polythiophene in the oxidized form, its high conductivity and an interesting electrochemical behaviour allow this material to use it for contemporary application. Therefore, its thermal analysis becomes crucial. The oxidant concentration dependant thermal analysis of PTh/PVAc studied in the present article. The PTh/PVAc composite films were synthesized by chemical polymerization method by using FeCl3 as an oxidant in organic medium. The two samples (S1 and S2) of composite were synthesized using 140 and 150 monomer to oxidant ratio respectively. The samples were characterized by FTIR, XRD and TG-DTA. The thermal properties of composites were studied from TG-DTA. It was found that the thermal properties are monomer to oxidant ratio dependent.